Practical Chinese usage : common words and phrases - Wu, Emma Lejun (London ; New York : Routledge, 2020)
"Practical Chinese Usage offers post-beginner to near advanced students of Chinese with a guide to the most frequently misused and confusing words in the language; Entries are arranged in alphabetical order for ease of reference; Sample sentences with Pinyin and English translations are provided after each explanation; Examples of typical mistakes made by students are clearly marked throughout; Each entry is annotated in accordance with the New HSK guidelines, indicating the level of difficulty. Practical Chinese Usage provides students of Chinese with the necessary tool to refine their use of expressions and synonyms in order to communicate effectively in the Chinese language"--
OCLC-licensed vendor bibliographic record.
Keywords: Chinese language -- Textbooks for foreign speakers -- English; Chinese language -- Usage; Chinese language -- Errors in usage; Chinese language -- Glossaries, vocabularies, etc; FOREIGN LANGUAGE STUDY / Chinese